Neuromuscular retraining in female adolescent athletes: Effect on athletic performance indices and noncontact anterior cruciate ligament injury rates - Noyes, F. R.; Barber-Westin, S. D. (Sports, 2015)
While many anterior cruciate ligament (ACL) prevention programs have been published, few have achieved significant reductions in injury rates and improvements in athletic performance indices; both of which may increase compliance and motivation of athletes to participate. A supervised neuromuscular retraining program (18 sessions) was developed, aimed at achieving both of these objectives. The changes in neuromuscular indices were measured after training in 1000 female athletes aged 13-18 years, and the noncontact ACL injury rate in 700 of these trained athletes was compared with that of 1120 control athletes. There were significant improvements in the drop-jump test, (p < 0.0001, effect size [ES] 0.97), the single-leg triple crossover hop (p < 0.0001, ES 0.47), the t-test (p < 0.0001, ES 0.64), the multi-stage fitness test (p < 0.0001, ES 0.57), hamstring strength (p < 0.0001), and quadriceps strength (p < 0.01). The trained athletes had a significant reduction in the noncontact ACL injury incidence rate compared with the controls (1 ACL injury in 36,724 athlete-exposures [0.03] and 13 ACL injuries in 61,244 exposures [0.21], respectively, p = 0.03). The neuromuscular retraining program was effective in reducing noncontact ACL injury rate and improving athletic performance indicators.